High Spatial Resolution MALDI‐MS Imaging in the Study of Membranous Nephropathy. Issue 1 (19th December 2018) - Smith, Andrew; L'Imperio, Vincenzo; Denti, Vanna; Mazza, Mariafrancesca; Ivanova, Mariia; Stella, Martina; Piga, Isabella; Chinello, Clizia; Ajello, Elena; Pieruzzi, Federico; Pagni, Fabio; Magni, Fulvio
Abstract : Purpose: Matrix‐assisted laser desorption/ionization mass spectrometry imaging (MALDI‐MSI) technology has advanced rapidly during recent years with the development of instruments equipped with low‐diameter lasers that are suitable for high spatial resolution imaging. This may provide significant advantages in certain fields of molecular pathology where more specific protein fingerprints of individual cell types are required, such as renal pathology. Experimental design: Here MALDI‐MSI analysis of a cohort of membranous nephropathy (MN) patients is performed among which patients either responded favorably (R; n  = 6), or unfavorably (NR; n  = 4), to immunosuppressive treatment (Ponticelli Regimen), employing a 10 µm laser spot diameter. Results: Specific tryptic peptide profiles of the different cellular regions within the glomerulus can be generated, similarly for the epithelial cells belonging to the proximal and distal tubules. Conversely, specific glomerular and sub‐glomerular profiles cannot be obtained while using the pixel size performed in previous studies (50 µm). Furthermore, two proteins are highlighted, sonic hedgehog and α‐smooth muscle actin, whose signal intensity and spatial localization within the sub‐glomerular and tubulointerstitial compartments differ between treatment responders and non‐responders. Conclusions and clinical relevance: The present study exemplifies the advantage of using high spatial resolution MALDI‐MSI for the study of MN and highlights that such findings have the potential to provide complementary support in the routine prognostic assessment of MN patients.